2017
DOI: 10.18639/onbt.2017.04.454505
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera in the management of oral submucous fibrosis

Abstract: Oral submucous fibrosis is a pre-malignant condition commonly prevalent in India, Pakistan, Taiwan and Sri Lanka. Patients characteristically exhibit progressive reduction in mouth opening. The disease has a high malignant potential and thus should be diagnosed and treated at the earliest. However, none of the currently used medical therapies show promising results. The current article briefly reviews the role of Aloe vera in the management of oral submucous fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The initial search yielded a total of 28 studies, of which 13 were duplicates and thus were excluded (Figure ). Following an initial screening of the titles and abstracts of the remaining 15 publications, eight studies were found irrelevant (seven reviews and one irrelevant trial) and were subsequently removed. The full‐texts of the remaining seven studies were sought and thoroughly read and assessed by the two authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search yielded a total of 28 studies, of which 13 were duplicates and thus were excluded (Figure ). Following an initial screening of the titles and abstracts of the remaining 15 publications, eight studies were found irrelevant (seven reviews and one irrelevant trial) and were subsequently removed. The full‐texts of the remaining seven studies were sought and thoroughly read and assessed by the two authors.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the effectiveness of aloe vera in the management of OSF is still controversial; and although some narrative reviews have briefly discussed the use of aloe vera for OSF, there has been no any systematic review with or without meta‐analysis that assessed the available evidence on the efficacy of aloe vera in OSF management. Therefore, the present systematic review and meta‐analysis sought to assess the efficacy of aloe vera on pain alleviation and clinical improvement in patients with OSF.…”
Section: Introductionmentioning
confidence: 99%
“…Review of literature reveals that Aloe vera appears to be promising in the management of OSMF. [12] The authors suggest that future research should focus on experimenting the combined actions of TSNs and Aloe vera in management of OSMF and OSCC. Also, more research needs be done to make TSNs bioavailable through oral route.…”
Section: Introductionmentioning
confidence: 99%